2016
DOI: 10.1007/s11661-016-3568-6
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure Evolution in the Near-Surface Region During Homogenization of a Twin-Roll Cast AlFeMnSi Alloy

Abstract: A near-surface deformed layer, comprising ultrafine grains of 50-500 nm diameters with the grain boundaries being decorated by a high population density of fine cubic a-Al 15 (FeMn) 3 Si 2 dispersoids and oxide/lubricant particles, was generated in a foil stock AlFeMnSi alloy during twin-roll casting due to severe shear deformation within the near-surface region. During a subsequent multi-step homogenization treatment at temperatures in the range of 713 K and 853 K (440°C and 580°C), the fine cubic a-Al 15 (Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…This was clearly shown in the works of Zhang et al and Donatus et al Most recently, it was observed that the manufacturing‐process induced near‐surface deformed layer (MPI‐NSDL) significantly affects the corrosion and electrochemical behaviour of this alloy. NSDL is produced by preferential deformation of the near surface region of an alloy during processes like rolling, extrusion, machining, and even mechanical grinding and polishing . However, the manufacturing process induced ones are usually more of a concern with regard to corrosion and electrochemistry.…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…This was clearly shown in the works of Zhang et al and Donatus et al Most recently, it was observed that the manufacturing‐process induced near‐surface deformed layer (MPI‐NSDL) significantly affects the corrosion and electrochemical behaviour of this alloy. NSDL is produced by preferential deformation of the near surface region of an alloy during processes like rolling, extrusion, machining, and even mechanical grinding and polishing . However, the manufacturing process induced ones are usually more of a concern with regard to corrosion and electrochemistry.…”
Section: Introductionsupporting
confidence: 57%
“…However, the manufacturing process induced ones are usually more of a concern with regard to corrosion and electrochemistry. The MPI‐NSDL exhibits different chemical and metallurgical characteristics . Thus, it is logical to conclude that the MPI‐NSDL will also have a strong influence on the silanization process of this alloy since it is strongly influenced by the composition at the metal surface.…”
Section: Introductionmentioning
confidence: 99%
“…Given that SLC sites are associated with more HE compared with other corrosion sites on the surfaces of Al alloys, the polished surface generated most intense sites of evolution hydrogen compared with the as‐received surface of the alloy. The as‐received surface of a rolled Al alloy is characterized by the presence of the NSDL that was induced by the rolling process during the production of the alloy . This NSDL, in the case of the investigated alloy, is composed of Mg‐rich bands (as typified by the results in Figure ) and an oxide layer that is far thicker than the one present on a polished surface of the alloy.…”
Section: Resultsmentioning
confidence: 92%
“…Severe localized corrosion in Al‐Cu‐Li alloys has been associated with hexagonal T1 phase (Al 2 CuLi), which is preferentially located in regions of high dislocation density 3–14 . This leads to severe localized corrosion 13,15,16 . According to literature, 17,18 T1 phase is initially anodic relatively to the matrix, but due to the high reactivity of lithium, its selective dissolution from T1 phase leads to its copper enrichment, polarity reversal, and, in turn, the dissolution of the surrounding matrix 16 .…”
Section: Introductionmentioning
confidence: 99%